Game of Life - "Harry, Lou" (New Delhi, 2006)
It S not just a game, it S your future. Here S how to make the most of it! College. Career. Marriage. Kids, retirement and beyond-your future success and happiness depends on how you play the game of Life, The real game of Life. There are exciting choices to be made and new paths to explore. How will you figure out what S best for you? Enter the game of Life. Playing this game is more than just a friendly diversion, it S your future examined every step of the way, from the first experiences away from childhood, to the last stumbles toward millionaire estates. In the game of Life you will find friendly advice, witty wisdom, and deep thoughts to guide you through all of life S leaps, bounds, big surprises and small victories, including the first day of your first job-how to fit in and get ahead starting from day one. The marriage express-so it S time to tie the knot, what are some questions that might help you be as successful in your personal life as you are in your career. Playing the market-should you or shouldn T you? And how to hold your head high whether bulls or bears are in control. Based on the ever-popular, and very insightful, Board game. The game of Life will guide you toward success and happiness, no matter what that means to you.
Keywords: College-Life